Authentic Assessment Implementation in Islamic Education Subject of Curriculum 2013 on SMA 1 Hutabargot Mandailing Natal - Asfiati Asfiati (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2020)
Implementation of authentic assessment is motivated by the emergence of a curriculum change from KTSP curriculum into the curriculum 2013. Curriculum 2013 seeks to enhance authentic assessment standards that emphasize on learning outcomes. This study aims to determine the implementation of authentic assessment on the Curriculum 2013 in state senior high school / SMA Negeri 1 Hutabargot, Mandailing Natal district. The research applies a descriptive qualitative method. The research subject is a teacher of Islamic education in state senior high school / SMA Negeri 1 Hutabargot, Mandailing Natal district who is known as a State Civil Apparatus. Data are collected through observation, interviews, and documentation. The results reveal that the implementation of authentic assessment on the Curriculum 2013 is appropriate to its techniques, instruments, and processes. Attitude assessment is obtained from observation using a checklist, while knowledge assessment is obtained from verbal and written tests, and skills assessment is obtained from a test, a scale list.